2000
DOI: 10.1002/1097-0029(20000615)49:6<511::aid-jemt2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function in the cerebral ganglion

Abstract: Evidence is reviewed to evaluate whether the term "brain" is justified in referring to the snail's cerebral ganglion. The focus of the review is terrestrial species, with particular attention given to the genus Helix. In accordance with a standard definition of "brain," the cerebral ganglion is found to be differentiated both structurally and functionally. It receives convergent sensory inputs from a variety of anterior sensory organs plus the posterior body wall. Its outputs comprise motor commands directed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 44 publications
(61 reference statements)
0
26
0
1
Order By: Relevance
“…In terrestrial gastropods, the importance of the procerebrum for olfactory information processing was shown (Delaney et al 1994;Gelperin 1999;Gelperin and Tank, 1990), and the neuroanatomy and function of the cerebrum with respect to olfactory information processing was reviewed by Chase (2000). However, only little is known about the olfactory pathway from the sensory cells to higher centres.…”
Section: Introductionmentioning
confidence: 54%
“…In terrestrial gastropods, the importance of the procerebrum for olfactory information processing was shown (Delaney et al 1994;Gelperin 1999;Gelperin and Tank, 1990), and the neuroanatomy and function of the cerebrum with respect to olfactory information processing was reviewed by Chase (2000). However, only little is known about the olfactory pathway from the sensory cells to higher centres.…”
Section: Introductionmentioning
confidence: 54%
“…4 A). Although we still do not know the precise quantitative relationship between the size of the neuron and its DNA content, such apparent inconsistency can be explained by the fact that approximately one-half of the neurons of the brain are composed of PC neurons that contain a diploid genome within their nuclei (Chase and Tolloczko, 1987;Gelperin and Tank, 1990;Chase, 2000). This preponderance of diploid PC neurons would have reduced the average DNA content in the brain as a whole.…”
Section: Dna Synthesis During Body Growthmentioning
confidence: 98%
“…2). Because the PC contains a large number of olfactory interneurons (Gelperin and Tank, 1990;Chase, 2000), our observation argues for the hypothesis by Gillette (1991) that the size of the body must be more faithfully reflected in the sizes of effector neurons than in the interneurons. In fact, we observed that the size of the neurons regulating the heart beat (LdWFamide-containing VGCs and achatin-I-containing neurons) was greater in the growthpromoted slugs than in the growth-suppressed slugs (Figs.…”
Section: Increase In the Size Of Ganglia And Neuronsmentioning
confidence: 99%
“…The local field potential (LFP) recorded on the PC exhibits spontaneous oscillation (~0.7Hz) induced by the synchronous activities of the inhibitory networks within the PC (Gelperin and Tank, 1990;Watanabe et al, 2008). It is thought that the oscillatory frequency of the LFP encodes the meaning/value of the odor that the tentacle detects (Kimura et al, 1998a;Chase, 2000;Inoue et al, 2006), and its change is thought to correspond to the decision-making that occurs just before the approach or avoidance of the odor sources (Samarova and Balaban, 2009). Both the superior and inferior tentacles innervate primarily to the terminal mass (TM) layer of the PC (Gelperin et al, 1993;Kawahara et al, 1997;Kimura et al, 1998b), where the olfactory information is transmitted to nonbursting neurons in the PC (Watanabe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%